Preparation method of environment-friendly waste magnesium-carbon brick regenerated low-temperature solidified unburned refractory brick

CN122647247BActive Publication Date: 2026-11-03ANGANG VESUVIUS REFRACTORY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611149456.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-31
Publication Date
2026-11-03
Estimated Expiration
2046-07-31

AI Technical Summary

Technical Problem

Existing technologies have low resource utilization rates, high energy consumption, and lack low-temperature chemical bonding regeneration pathways targeting their unique microstructure, resulting in a waste utilization rate of no more than 30% and no fundamental improvement in energy consumption.

Method used

Using 65%~75% waste magnesia-carbon bricks as the main raw material, combined with modified phosphate composite binder and nano-reinforced powder, non-fired refractory bricks are prepared by room temperature pressure molding followed by low temperature curing, avoiding the high temperature sintering process. By utilizing the synergistic effect of modified phosphate composite binder and nano-reinforced powder, a balance between high waste content, low energy consumption and high performance is achieved.

Benefits of technology

Waste utilization rate increased to 75%, energy consumption reduced by more than 80%, and the comprehensive energy consumption per unit product reduced to about 0.5 GJ/t. Its performance is comparable to that of traditional 1600℃ fired bricks, and it is suitable for high-temperature parts such as working linings of metallurgical steel ladles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122647247B_ABST
    Figure CN122647247B_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of environment-friendly waste magnesium-carbon brick regenerated low-temperature solidified unfired refractory brick and belongs to the technical field of refractory material preparation. In the application, waste magnesium-carbon bricks are crushed and sieved to obtain three levels of raw materials, which are matched according to residual carbon content of 3% to 12%; then, waste magnesium-carbon brick aggregates, modified phosphate composite binding agent, nano-enhanced micro powder and auxiliary mineralizing agent are mixed; green bodies are formed by normal-temperature pressure molding; and low-temperature heat preservation solidification is carried out to obtain unfired refractory bricks. The application can realize the recycling of waste magnesium-carbon bricks, increase the utilization rate of waste materials from 30% to 65-75%, reduce energy consumption by about 80%, and the volume density of finished products is greater than or equal to 2.85 g / cm 3 , the normal-temperature bending resistance is greater than or equal to 15 MPa, the slag resistance is equivalent to that of traditional fired bricks, and the application can be used for metallurgical steel ladle working lining.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of refractory material preparation technology, specifically to a method for preparing environmentally friendly waste magnesia-carbon bricks that are recycled at low temperatures and cured without burning. Background Technology

[0002] Magnesia-carbon bricks are non-fired composite refractory materials made primarily from high-purity fused magnesia or sintered magnesia and flake graphite, combined with organic binders such as phenolic resin or modified bitumen. They are formed under pressure at room temperature and then baked at approximately 250°C. Due to the excellent slag erosion resistance imparted by the high melting point of magnesium oxide (approximately 2800°C) and the high thermal conductivity and non-wetting properties of graphite, magnesia-carbon bricks are widely used in key working linings of high-temperature metallurgical kilns such as converters, electric arc furnaces, and ladles, making them an indispensable core refractory material in the modern steelmaking industry.

[0003] According to industry statistics, the amount of waste magnesia-carbon bricks generated globally each year due to the replacement of linings in metallurgical kilns is in the millions of tons. These waste magnesia-carbon bricks still contain a large amount of unconsumed high-purity magnesium oxide particles (typically 75%–85%) and some residual graphite carbon (the content varies from 3% to 12% depending on the application), possessing significant recycling value. However, the current industry disposal of waste magnesia-carbon bricks mainly relies on landfilling or low-value crushing and sales, resulting in a generally low resource utilization rate.

[0004] For the resource utilization of waste magnesia-carbon bricks, the main existing technical routes are as follows:

[0005] ① Magnesia recovery route combining flotation and high-temperature combustion: This route removes graphite impurities through physical flotation, followed by a combustion decarburization process to obtain recycled magnesia powder containing approximately 81.56% (flotation) to over 93% (combustion) magnesium oxide. This recycled magnesia is then used as a substitute for virgin magnesia in refractory product manufacturing. While this route can obtain high-purity recycled magnesia, the process is lengthy, with high reagent consumption during flotation and high energy consumption during combustion decarburization. Furthermore, the final product still needs to enter a traditional high-temperature sintering production line above 1500℃, resulting in limited improvement in overall energy consumption and carbon emission levels (see RecyclingMagnesia Carbon Refractory Bricks from the Steel Industry, 2025).

[0006] ② The direction of using waste magnesia brick powder for magnesium phosphate cement mortar: This route uses the fine powder obtained by crushing and screening waste magnesia bricks as an active raw material, which is mixed with phosphate binder to prepare magnesium phosphate cement mortar, which is applied to building repair, precast components and other scenarios. This route has confirmed that a stable hydration reaction can occur between the recycled magnesium oxide and phosphate in waste magnesia bricks (see Study on Hydration Activity, Mechanical Properties and Long-Term Performance of Waste Magnesia Brick Powder for Magnesia Phosphate Cement Mortar, Construction and Building Materials, 2023, 402, 133019). However, the final product of this route is mortar rather than refractory bricks, and the waste utilization is limited to fine powder, which does not give full play to the refractory performance inheritance of waste magnesia-carbon bricks at the coarse aggregate scale. Moreover, the application scenarios of mortar are completely different from those of high-temperature metallurgical parts such as steel ladle linings.

[0007] ③ Limited-dosage recycled aggregate magnesia-carbon brick regeneration direction: This route involves crushing waste magnesia-carbon bricks to obtain recycled aggregate, which is then mixed with virgin magnesia and graphite in a certain proportion to prepare magnesia-carbon bricks containing recycled raw materials. (Volkov-Husovi) A 2022 study investigated the effects of recycled aggregate content ranging from 10% to 30% on the physical and mechanical properties and slag erosion resistance of magnesia-carbon bricks. The study concluded that recycled aggregate content below 30% had no significant negative impact on magnesia-carbon brick performance, and recommended 30% as the upper limit. International refractory companies such as RHI Magnesita also control the recycled raw material content in their commercial products to below 30%, using a tempered magnesia-carbon brick process, still relying on modified bitumen binder systems and a baking and curing process at around 250°C (RHI Magnesita Bulletin, 2024). The fundamental limitation of this approach is the low ceiling for recycled aggregate content (≤30%), which rigidly restricts the resource utilization rate of waste magnesia-carbon bricks. Furthermore, this approach still uses organic binders such as bitumen or phenolic resin, leading to volatile organic compound emissions during curing, and the 250°C baking temperature is close to the oxidation-sensitive range of residual graphite carbon.

[0008] A comprehensive analysis of existing technologies reveals three main shortcomings in the resource utilization of waste magnesia-carbon bricks: First, the utilization rate of waste materials is low. Whether it is the flotation recovery route or the recycled aggregate route, the maximum utilization rate of waste magnesia-carbon bricks is generally no more than 30%, which creates a significant supply-demand contradiction with the annual waste generation of millions of tons.

[0009] Secondly, the recycling process is energy-intensive. The flotation recovery route still needs to enter a high-temperature sintering line at over 1500℃. Although the recycled aggregate route avoids high-temperature sintering, it still requires a 250℃ asphalt baking process, so the overall energy consumption level has not been fundamentally improved.

[0010] Third, there is a lack of a dedicated binder system for the unique microstructure of waste magnesia-carbon bricks. After long-term high-temperature service, the surface of the magnesium oxide particles in waste magnesia-carbon bricks undergoes sufficient high-temperature activation, and the residual graphite carbon layer exhibits a unique porous structure. If this dual microstructure feature of highly reactive magnesium oxide particles + porous residual carbon layer can be specifically utilized, it will open up a completely new low-temperature chemical bonding regeneration pathway.

[0011] Therefore, how to provide a method for preparing environmentally friendly waste magnesia-carbon bricks that are recycled at low temperatures and cured into non-fired refractory bricks, achieving a triple unity of high waste content, low energy consumption, and high performance, is a technical problem that urgently needs to be solved by those skilled in the art. Summary of the Invention

[0012] In view of this, the present invention provides a method for preparing environmentally friendly recycled low-temperature curing non-fired refractory bricks from waste magnesia-carbon bricks. The method uses waste magnesia-carbon bricks (65%–75% by mass) as the main raw material, combined with a modified phosphate composite binder and nano-reinforcing powder. After being molded under pressure at room temperature, the bricks are cured at low temperature to obtain non-fired refractory bricks. This method achieves a triple balance of high waste content, low energy consumption, and high performance.

[0013] To achieve the above objectives, the present invention adopts the following technical solution: A method for preparing environmentally friendly recycled low-temperature curing non-fired refractory bricks from waste magnesia-carbon bricks, characterized by comprising the following steps: (1) The waste magnesia-carbon bricks are sorted according to the residual carbon content to obtain waste magnesia-carbon brick material batches with a residual carbon content of 3%~12%. The material batches are then crushed and graded by a vibrating screen to obtain three grades of raw materials: coarse aggregate, medium aggregate, and fine powder. The coarse aggregate, medium aggregate, and fine powder are then mixed to obtain waste magnesia-carbon brick aggregate. (2) The waste magnesia-carbon brick aggregate, modified phosphate composite binder, nano-reinforced powder and auxiliary mineralizer are mixed to obtain a mixture; (3) The mixture is pressed and molded at room temperature to obtain a green body; (4) The green brick is heated and kept warm to solidify, and then naturally cooled to room temperature to obtain environmentally friendly waste magnesia-carbon bricks recycled at low temperature and non-fired refractory bricks.

[0014] Furthermore, when the waste magnesia-carbon bricks mentioned in step (1) are crushed, the waste magnesia-carbon bricks are first crushed by a jaw crusher to block material with a particle size of no more than 50 mm, and then crushed by an impact crusher to block material with a particle size of no more than 10 mm. The coarse aggregate has a particle size of 1mm to 3mm, the medium aggregate has a particle size of 0.1mm to 1mm, and the fine powder has a particle size of no more than 0.075mm. The residual carbon content of the coarse aggregate, medium aggregate, and fine powder is 3% to 12%, and the residual carbon content of the coarse aggregate, medium aggregate, and fine powder is uniformly controlled at the batch level, rather than being independently controlled for the three raw materials. That is, the residual carbon content of the coarse aggregate, medium aggregate, and fine powder is consistent.

[0015] The mass ratio of coarse aggregate, medium aggregate, and fine powder in the waste magnesia-carbon brick aggregate is 30~40:30~40:20~30.

[0016] Furthermore, the waste magnesium-carbon brick aggregate is pre-coated with a composite aqueous solution of citric acid and phenolic resin for 10 to 30 minutes to resist hydration. In the composite aqueous solution of citric acid and phenolic resin, the mass concentration of citric acid is 0.5%~2%, and the mass concentration of phenolic resin is 1%~3%.

[0017] In this invention, there is no theoretical conflict between the anti-hydration pre-coating treatment and the subsequent wet mixing operation; they act on different reaction pathways and time scales. The purpose of the anti-hydration pre-coating treatment is to inhibit the uncontrolled bulk hydration reaction (MgO + H2O → Mg(OH)2) that occurs in the highly reactive magnesium oxide in waste magnesia-carbon brick aggregate due to the slow absorption of environmental moisture during storage, transportation, and mixing at room temperature. This uncontrolled hydration has no bonding contribution and is accompanied by volume expansion, which easily leads to aggregate pulverization and green body cracking. Citric acid chelates on the surface of magnesium oxide through carboxylic acid groups to form a passivation layer, while phenolic resin forms a hydrophobic film. The two work synergistically and selectively delay the aforementioned slow bulk hydration pathway. The subsequent wet mixing involves adding water at 3% to 8% of the total raw material mass and mixing for 3 to 8 minutes, which is a short-term controlled operation. Its purpose is to trigger a rapid acid-base bonding reaction between magnesium oxide and the phosphate main agent, generating strongly bonded phases such as magnesium potassium phosphate hexahydrate. Because the phosphate-base bonding reaction is driven by the low pH of the liquid phase and its reaction rate is much higher than that of the neutral bulk phase hydration reaction, and because the anti-hydration coating is partially dissolved and activated under the controlled wet mixing of mechanical shear and acidic phosphate solution, the phosphate bonding reaction can still proceed normally. The presence of the anti-hydration coating causes the reaction on the magnesium oxide surface to preferentially proceed along the phosphate bonding pathway rather than along the ineffective bulk phase hydration pathway, thereby inhibiting destructive hydration without weakening phosphate bonding. This breaks with conventional understanding in the field, reversing the conflict between the two in conventional understanding into a complementarity.

[0018] Furthermore, the mixture described in step (2) consists of the following raw materials in parts by weight: 65-75 parts of waste magnesia-carbon brick aggregate, 8-15 parts of modified phosphate composite binder, 1-5 parts of nano-reinforced powder, and 1-3 parts of auxiliary mineralizer; The modified phosphate composite binder is composed of a phosphate-containing main agent and a retarding modifier.

[0019] Furthermore, the nano-reinforced powder is nano-silica and / or nano-alumina, and the specific surface area of ​​the nano-reinforced powder is not less than 50 m². 2 / g, with a D50 particle size of no more than 500nm; Preferably, when the nano-reinforced powder is composed of nano-silica and nano-alumina, the mass ratio of nano-silica to nano-alumina is 1:0.5 to 1:2.

[0020] The auxiliary mineralizer is ultrafine metakaolin powder or Class I fly ash ultrafine powder, and the specific surface area of ​​the auxiliary mineralizer is not less than 600 m². 2 / kg.

[0021] The Grade I fly ash ultrafine powder is obtained by ultrafine grinding of Grade I fly ash conforming to GB / T 1596-2017. Its fineness, measured by the residue on a 45μm square hole sieve, is no more than 12%, its loss on ignition is no more than 5%, and the total mass fraction of silica, alumina, and ferric oxide is no less than 70%, with a D50 particle size of 3μm to 10μm. The metakaolin ultrafine powder has a D50 particle size of 2μm to 8μm, and the total mass fraction of active silica and active alumina is no less than 90%.

[0022] Furthermore, the mass ratio of the phosphate main agent to the retarding modifier in the modified phosphate composite binder is 60~80:20~40; The phosphate main agent is any one or a mixture of potassium dihydrogen phosphate, ammonium dihydrogen phosphate, aluminum phosphate, and magnesium dihydrogen phosphate; The retarding modification component is any two or more of water glass, borax, and citric acid.

[0023] Preferably, the modulus of the water glass is 2.4 to 3.0. Furthermore, the mixing in step (2) involves first dry mixing each raw material for 3 to 5 minutes, and then adding water equivalent to 3% to 8% of the total mass of the raw materials and wet mixing for 3 to 8 minutes.

[0024] Furthermore, the pressure applied during the pressing process in step (3) is 80 MPa to 120 MPa, and the density of the green body is not less than 2.80 g / cm³. 3 .

[0025] Furthermore, the green body described in step (4) is aged at room temperature for 24h~48h before being heat-insulated and cured, and then pre-dried at 50℃~80℃ for 4h~8h.

[0026] Furthermore, the heating temperature for heat preservation and curing in step (4) is 180℃~220℃, and the heat preservation and curing time is 8h~24h.

[0027] Furthermore, the recycled low-temperature curing non-fired refractory bricks prepared by this invention can be used in the working lining of metallurgical steel ladles.

[0028] The beneficial effects of this invention are as follows: 1. In this invention, the resource utilization rate of waste magnesia-carbon bricks can be increased from no more than 30% in the existing technology to about 75%, the waste utilization rate is increased by more than two times, the amount of waste consumed per unit product is significantly increased, and an effective disposal path is provided for the annual production of millions of tons of waste magnesia-carbon bricks. Each ton of finished bricks can consume 650kg to 750kg of waste magnesia-carbon bricks. Based on the national annual production of 1.5 million tons of steel ladle unfired bricks, it can consume about 1 million tons of waste magnesia-carbon bricks.

[0029] 2. The present invention eliminates the traditional high-temperature sintering process above 1500℃ during the preparation process, saving about 80% of energy compared to the traditional magnesia brick firing process, and about 20% energy compared to the existing recycled aggregate magnesia-carbon brick 250℃ asphalt baking process. The comprehensive energy consumption per unit product is reduced from about 2.5 GJ / t of traditional magnesia bricks to about 0.5 GJ / t of the present invention. At the same time, the emission of volatile organic compounds in the asphalt baking process is avoided, and the carbon dioxide equivalent emission per unit product is reduced by about 60%, realizing low-carbon green production.

[0030] 3. The modified phosphate composite binder used in this invention, through the synergistic effect of the retarding modifying components, extends the initial setting time between phosphate and highly reactive magnesium oxide particles from no more than 5 minutes in the unmodified system to more than 30 minutes. The operable process time window of the mixture is expanded from the original level that could not be industrialized to the level that is suitable for continuous production lines, completely solving the technical problem of flash condensation and providing an operable process time window for industrial continuous production.

[0031] 4. The unfired refractory bricks prepared by the method of the present invention, upon testing, have a bulk density of not less than 2.85 g / cm³. 3 It has a room temperature flexural strength of not less than 15MPa, a room temperature compressive strength of not less than 80MPa, a high temperature flexural strength of not less than 10MPa at 1400℃, and slag erosion resistance comparable to traditional 1600℃ fired magnesia bricks (erosion index ratio of 0.95~1.00). It has a water-cooled thermal shock resistance of not less than 20 cycles at 1100℃, and a performance stability variation coefficient of not more than 7%. It can be directly used as a permanent working lining for metallurgical steel ladles, and can also be extended to working linings for high-temperature parts such as electric furnace walls and continuous casting tundishes.

[0032] 5. The method provided by this invention has mild process parameters and low equipment dependence. The required equipment, such as crushers, mixers, hydraulic presses, and resistance furnaces, are all existing standard production line equipment in the refractory materials industry. There is no need to build new sintering tunnel kilns or oxidation protective atmosphere systems. It can be directly implemented on existing non-fired brick production lines, and the threshold for industrialization is low. Attached Figure Description

[0033] Figure 1 This is a flowchart illustrating the preparation process of environmentally friendly waste magnesia-carbon bricks recycled at low temperatures to form non-fired refractory bricks, as described in this invention.

[0034] Figure 2 This is a particle morphology diagram of waste magnesia-carbon brick aggregate in an embodiment of the present invention.

[0035] Figure 3 This is a scanning electron microscope (SEM) microstructure diagram of the unburned refractory brick in Embodiment 1 of the present invention; it shows the spatial distribution relationship of the residual graphite carbon layer, regenerated magnesium oxide particles and phosphate-bound phase.

[0036] Figure 4 The bar charts show the key performance comparison of the unfired refractory bricks prepared in Examples 1-3 and Comparative Examples 1-5 of this invention; where (a) is the bulk density, (b) is the apparent porosity, (c) is the flexural strength at room temperature and at 1400℃, and (d) is the slag erosion resistance index and the number of thermal shocks.

[0037] Figure 5 This is an X-ray diffraction phase analysis diagram of the unburned refractory brick prepared in Example 1 of the present invention after curing. Detailed Implementation

[0038] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0039] The residual carbon content grading of waste magnesia-carbon brick aggregate in this invention is specifically implemented in the following manner: First, the waste magnesia-carbon bricks are sorted according to their original service location. Due to the different oxygen partial pressure and temperature gradients they experienced during service, the residual graphite carbon content of the waste bricks in the slag line, ladle wall, and bottom of the ladle shows a regular difference. Specifically, the residual carbon content of the waste bricks in the lightly oxidized layer of the slag line is 3%~5%, the residual carbon content of the waste bricks in the middle layer of the ladle wall is 5%~8%, and the residual carbon content of the waste bricks in the deep unoxidized layer of the bottom of the ladle is 8%~12%. After sorting, the residual carbon content of each batch was determined according to the loss on ignition method in GB / T 2999-2002. Waste bricks with residual carbon content falling within the range of 3% to 12% were grouped into the same batch in increments of 2% to 3%. The waste bricks in the same batch were crushed and vibrated to obtain three grades of raw materials: coarse aggregate, medium aggregate, and fine powder. Since the three grades of raw materials came from the same batch of residual carbon materials, their residual carbon content was consistent and fell within the same control range. That is, the residual carbon content was not controlled independently for the three grades of raw materials: coarse aggregate, medium aggregate, and fine powder, but was uniformly controlled at the batch level.

[0040] Example 1 Environmentally friendly recycled low-temperature curing non-fired refractory bricks made from waste magnesia-carbon bricks were prepared using the following parts by weight of raw materials: 70 parts of waste magnesia-carbon brick aggregate (with a mass ratio of coarse aggregate, medium aggregate, and fine powder of 35:35:30, the coarse aggregate, medium aggregate, and fine powder forming a three-level particle packing system and matching the optimal densification path of the Andreasen packing distribution curve q=0.30, the coarse aggregate particle size is 2mm, the medium aggregate particle size is 0.5mm, the fine powder particle size is no greater than 0.075mm, and the residual graphite carbon content of each aggregate is controlled within the range of 5% to 7%); 12 parts of modified phosphate composite binder (with 70wt% potassium dihydrogen phosphate, 15wt% water glass, 10wt% borax, and 5wt% citric acid); 3 parts of nano-reinforced powder (with a mass ratio of nano-silica to nano-alumina of 1:1); and 2 parts of auxiliary mineralizer (metakaolin ultrafine powder).

[0041] The preparation method of environmentally friendly recycled low-temperature curing non-fired refractory bricks from waste magnesia-carbon bricks is as follows: (1) Aggregate pretreatment and batching: The waste magnesia-carbon bricks are first crushed into blocks with a particle size of no more than 50 mm by a jaw crusher, and then crushed into blocks with a particle size of no more than 10 mm by an impact crusher. Then, the coarse aggregate, medium aggregate and fine powder are obtained by screening. After batching in a mass ratio of 35:35:30, the waste magnesia-carbon brick aggregates are put into a V-type mixer for premixing for 3 minutes until the aggregates are evenly distributed. The premixing speed is 25 r / min.

[0042] (2) Preparation of mixture: The premixed waste magnesium carbon brick aggregate, modified phosphate composite binder, nano-reinforced micro powder and auxiliary mineralizer are put into the forced countercurrent mixer in sequence. First, dry mix for 3 minutes, and then add deionized water equivalent to 5% of the total mass of raw materials as molding water while stirring. Wet mix for 5 minutes until the mixture is in a plastic state that can be kneaded into a ball by hand and dispersed when dropped.

[0043] (3) Room temperature pressure molding: The mixture is loaded into a metal mold and molded at room temperature with a molding pressure of 100MPa on a 200t hydraulic press to obtain a green body of a standard brick with dimensions of 230mm×114mm×65mm.

[0044] (4) Stage curing and low temperature curing: The green bricks are first aged at room temperature (25℃, relative humidity 60%) for 36 hours; then pre-dried in a drying oven at 65℃ for 6 hours; finally, the pre-dried green bricks are sent into a box-type resistance furnace and kept at 200℃ for 16 hours. After naturally cooling to room temperature, environmentally friendly waste magnesia-carbon bricks are recycled and cured at low temperature without burning.

[0045] Performance testing: The unfired refractory brick prepared in Example 1 was tested, and its bulk density was 2.92 g / cm³. 3 The apparent porosity is 11.5%, the flexural strength at room temperature is 18.2 MPa, the compressive strength at room temperature is 92 MPa, the flexural strength at 1400℃ is 12.5 MPa, the slag erosion resistance index at 1600℃ (measured by the VOD steel slag static crucible method, with 1.00 as the baseline in this example) is 1.00, the number of water-cooled thermal shock cycles at 1100℃ is 25, and the coefficient of variation for the performance stability of 10 repeated batches is 5.2%.

[0046] like Figure 5 XRD phase analysis showed that the main bound phases were magnesium potassium phosphate hexahydrate (i.e., K-struvite, MgKPO4·6H2O) and magnesium triphosphate pentahydrate. The residual graphite carbon layer was intact and no obvious oxidation weight loss was observed (TGA measured the weight loss rate in the range of 180℃ to 220℃ to be no more than 0.3%).

[0047] like Figure 3 Scanning electron microscopy characterization showed that the residual graphite carbon layer on the surface of the waste magnesia-carbon brick particles was completely preserved. The waste magnesia-carbon brick aggregate was embedded in a three-dimensional bonding network composed of needle-shaped magnesium potassium phosphate hexahydrate crystalline phase. The nano-reinforced powder was uniformly filled in the gaps and micropores of the needle-shaped bonding phase, and the interface was tightly bonded.

[0048] Example 2 The technical solution is basically the same as that in Embodiment 1, except that: Environmentally friendly recycled low-temperature curing non-fired refractory bricks made from waste magnesia-carbon bricks were prepared using the following parts by weight: 65 parts of waste magnesia-carbon brick aggregate (coarse aggregate, medium aggregate, and fine powder in a mass ratio of 30:40:30; coarse aggregate particle size of 1 mm; medium aggregate particle size of 0.1 mm; fine powder particle size of no more than 0.075 mm; residual graphite carbon content of each aggregate level was controlled at 3%; corresponding to the source of waste bricks in the light oxide layer of the slag line); 15 parts of modified phosphate composite binder (ammonium dihydrogen phosphate accounting for 65%, water glass 20%, and citric acid 15%); 1 part of nano-reinforced powder (nano silica and nano alumina in a mass ratio of 1:0.5); and 1 part of auxiliary mineralizer (grade I fly ash ultrafine powder).

[0049] The molding pressure in step (3) is 80 MPa; the green body aging time in step (4) is 48 h, the pre-drying temperature is 50 °C and the time is 8 h, and the low-temperature curing temperature is 180 °C and the time is 24 h.

[0050] Performance testing: The unfired refractory brick prepared in Example 2 was tested, and its bulk density was 2.88 g / cm³. 3 The apparent porosity is 12.8%, the flexural strength at room temperature is 15.6 MPa, the compressive strength at room temperature is 82 MPa, the flexural strength at 1400℃ is 10.8 MPa, the slag erosion resistance index at 1600℃ is 0.95, the number of water-cooled thermal shock cycles at 1100℃ is 22, and the coefficient of variation of performance stability is 6.8%.

[0051] XRD phase analysis showed that the main bound phase was magnesium ammonium phosphate hexahydrate (struvite, MgNH4PO4·6H2O), with the residual graphite carbon layer intact and no obvious oxidation weight loss observed. Scanning electron microscopy characterization showed that the phosphate bound phase consisted of interwoven needle-like crystals, with nano-reinforcing powder filling the micropores between the needle-like crystals. The aggregate particles and the bound phase were tightly bonded at the interface, with no obvious interfacial gaps.

[0052] Example 2, due to its high phosphate main agent mass fraction and low content of nano-reinforcing powder and auxiliary mineralizer, exhibits the characteristics of high binder content and low densification reinforcement at the lower end of the process, which can still meet the basic usage requirements of ladle working lining.

[0053] Example 3 The technical solution is basically the same as that in Embodiment 1, except that: Environmentally friendly recycled low-temperature curing non-fired refractory bricks made from waste magnesia-carbon bricks were prepared using the following parts by weight of raw materials: 75 parts of waste magnesia-carbon brick aggregate (coarse aggregate, medium aggregate, and fine powder in a mass ratio of 40:30:20; coarse aggregate particle size 3mm; medium aggregate particle size 1mm; fine powder particle size no greater than 0.075mm; residual graphite carbon content of each aggregate level controlled at 12%, corresponding to the source of waste bricks in the deep unoxidized layer of the bottom layer); 8 parts of modified phosphate composite binder (75% aluminum phosphate, 15% water glass, and 10% borax); 5 parts of nano-reinforced powder (nano silica and nano alumina in a mass ratio of 1:2); 3 parts of auxiliary mineralizer (metakaolin ultrafine powder).

[0054] The molding pressure in step (3) is 120 MPa; the green body aging time in step (4) is 24 h, the pre-drying temperature is 80 °C and the time is 4 h, and the low-temperature curing temperature is 220 °C and the time is 8 h.

[0055] Performance testing: The unfired refractory brick prepared in Example 3 was tested, and its bulk density was 2.95 g / cm³.3 The apparent porosity is 11.2%, the flexural strength at room temperature is 17.5 MPa, the compressive strength at room temperature is 88 MPa, the flexural strength at 1400℃ is 11.8 MPa, the slag erosion resistance index at 1600℃ is 0.98, the number of water-cooled thermal shock cycles at 1100℃ is 24, and the coefficient of variation of performance stability is 5.5%.

[0056] XRD phase analysis showed that the main bonding phases were magnesium triphosphate pentahydrate (Mg3(PO4)2·5H2O) and aluminum phosphate phase, with the residual graphitic carbon layer intact. TGA analysis showed that the weight loss rate in the temperature range of 180℃ to 220℃ was no more than 0.5%. Scanning electron microscopy characterization showed that the phosphate bonding phase had a dense granular morphology, and nano-alumina formed a bridging layer at the bonding phase interface. The aggregate had a high packing density, and the number of macroscopic crack defects was reduced by about 15% compared with Example 1.

[0057] Example 3, with its waste content reaching the upper limit of 75% and nano-reinforced powder content reaching the upper limit of 5%, exhibits the characteristics of high waste disposal and high densification at the upper end of the process, making it a preferred process route that balances resource utilization and product performance.

[0058] Example 4 The technical solution is basically the same as that in Example 1, except that: after the aggregate screening and matching in step (1) and before the preparation of the mixture in step (2), an anti-hydration pre-coating treatment is added: the waste magnesium carbon brick aggregate after screening and matching is immersed in a composite aqueous solution with a citric acid mass concentration of 1.5% and a phenolic resin mass concentration of 2% for 20 minutes for anti-hydration pre-coating treatment, and then dried at 110℃ for 2 hours to obtain waste magnesium carbon brick aggregate with an anti-hydration layer on the surface.

[0059] Performance testing: The unfired refractory brick prepared in Example 4 was tested, and its bulk density was 2.91 g / cm³. 3 The apparent porosity is 11.3%, the room temperature flexural strength is 18.5 MPa, the room temperature compressive strength is 93 MPa, the high temperature flexural strength at 1400℃ is 12.6 MPa, the slag erosion resistance index at 1600℃ is 1.01, the number of water-cooled thermal shock cycles at 1100℃ is 26, and the performance stability coefficient of variation is 4.8%.

[0060] Further testing was conducted to assess the effectiveness against hydration. After the aggregates were placed in a constant temperature and humidity chamber at 40°C and 90% relative humidity for 72 hours, their hydration weight gain was measured. The hydration weight gain of the aggregates without anti-hydration pre-coating treatment (Example 1) was 2.6%, while the hydration weight gain of the aggregates with anti-hydration pre-coating treatment (Example 4) was reduced to 0.4%.

[0061] After placing the green body in an environment with a relative humidity of 80% for 30 days, the retention rate of flexural strength at room temperature was measured. The retention rate was 82% in Example 1 and 96% in Example 4.

[0062] The above results show that the hydration-resistant pre-coating treatment, while inhibiting the uncontrolled hydration of waste magnesia-carbon brick aggregate, did not weaken the bonding reaction between phosphate and magnesium oxide in the subsequent wet mixing step (2). The mechanical and slag-resistant properties of Example 4 are comparable to or even slightly better than those of Example 1, proving that there is no theoretical conflict between the hydration-resistant pre-coating treatment and the subsequent wet mixing operation.

[0063] Comparative Example 1 The technical solution is basically the same as that in Embodiment 1, except that: Environmentally friendly recycled low-temperature curing non-fired refractory bricks made from waste magnesia-carbon bricks were prepared using the following parts by weight of raw materials: The mixture consists of 30 parts waste magnesia-carbon brick aggregate, 40 parts virgin fused magnesia (replacing part of the aggregate), 12 parts modified phosphate composite binder, 3 parts nano-reinforced powder, and 2 parts auxiliary mineralizer. The content of waste magnesia-carbon brick aggregate is reduced to 30% (corresponding to the conventional upper limit of existing recycled aggregate magnesia-carbon brick technology).

[0064] Performance testing: The unfired refractory brick prepared in Comparative Example 1 was tested and found to have a bulk density of 2.82 g / cm³. 3 The apparent porosity is 14.5%, the flexural strength at room temperature is 12.4 MPa, the compressive strength at room temperature is 65 MPa, the flexural strength at 1400℃ is 7.5 MPa, the slag erosion resistance index at 1600℃ is 0.82, the number of water-cooled thermal shock cycles at 1100℃ is 15, and the coefficient of variation of performance stability is 7.5%.

[0065] The room temperature flexural strength of Comparative Example 1 was only 68% of that of Example 1, and the high temperature flexural strength at 1400℃ was only 60% of that of Example 1.

[0066] Comparative Example 2 The technical solution is basically the same as that in Embodiment 1, except that: Environmentally friendly recycled low-temperature curing non-fired refractory bricks made from waste magnesia-carbon bricks were prepared using the following parts by weight of raw materials: The mixture consists of 70 parts waste magnesia-carbon brick aggregate, 12 parts modified bitumen binder, 3 parts nano-reinforcing powder, and 2 parts auxiliary mineralizer. The modified bitumen binder is a medium-temperature coal tar pitch with a softening point of 85℃ and a fixed carbon content of 55%, modified with 5% phenolic resin. In other words, the modified phosphate composite binder replaces the traditional modified bitumen binder (corresponding to the existing commercial non-fired magnesia-carbon brick binder system).

[0067] In step (4), curing is performed by heat preservation at 250℃ for 16 hours.

[0068] Performance testing: The unfired refractory brick prepared in Comparative Example 2 was tested and found to have a bulk density of 2.78 g / cm³. 3 The apparent porosity is 16.8%, the flexural strength at room temperature is 10.8 MPa, the compressive strength at room temperature is 58 MPa, the flexural strength at 1400℃ is 6.2 MPa, the slag erosion resistance index at 1600℃ is 0.75, the number of water-cooled thermal shock cycles at 1100℃ is 12, and the coefficient of variation of performance stability is 8.5%.

[0069] In Comparative Example 2, the residual graphite carbon oxidation weight loss rate during baking at 250°C reached 2.8% (measured by TGA), which was significantly higher than the 0.3% in Example 1.

[0070] Comparative Example 3 The technical solution is basically the same as that in Example 1, except that no nano-reinforced powder is added.

[0071] Performance testing: The unfired refractory brick prepared in Comparative Example 3 was tested and found to have a bulk density of 2.65 g / cm³. 3 The apparent porosity is 19.2%, the flexural strength at room temperature is 8.5 MPa, the compressive strength at room temperature is 45 MPa, the flexural strength at 1400℃ is 5.5 MPa, the slag erosion resistance index at 1600℃ is 0.68, the number of water-cooled thermal shock cycles at 1100℃ is 8, and the coefficient of variation of performance stability is 12.0%.

[0072] The apparent porosity of Comparative Example 3 increased by 67% compared to Example 1, while the slag resistance index decreased by 32%, indicating that the nano-reinforced powder plays a crucial role in filling the apparent porosity and acting as a dense barrier against slag.

[0073] Comparative Example 4 The technical solution is basically the same as that in Example 1, except that the waste magnesia-carbon brick aggregate is not graded for residual carbon content, and the residual carbon content mixture obtained from the crusher outlet is used directly (the measured residual carbon content distribution range is 3% to 15%).

[0074] Performance testing: The unfired refractory bricks prepared in Comparative Example 4 were tested in 10 repeated batches, and the average bulk density was 2.70 g / cm³. 3 The average apparent porosity was 17.5%, the average flexural strength at room temperature was 11.2 MPa, the average slag erosion resistance index at 1600℃ was 0.78, and the coefficient of variation of performance stability was as high as 26.5% (5.2% in Example 1).

[0075] The coefficient of variation for performance stability in Comparative Example 4 increased by more than 400% compared to Example 1, demonstrating the decisive role of residual carbon content grading and sieving in the stability of industrial batches.

[0076] Comparative Example 5 The technical solution is basically the same as that in Example 1, except that the modified phosphate composite binder is replaced with an aqueous solution of potassium dihydrogen phosphate (i.e., without any retarding modification components).

[0077] Performance testing: In Comparative Example 5, during the wet mixing process in step (2), the temperature of the mixture rapidly increased from 25°C to 48°C within 3 minutes after adding water. The mixture instantly hardened and clumped, making it impossible to load into the mold for pressing and molding. The preparation process was interrupted, and a complete green body was not obtained. This phenomenon indicates that there is a serious flash-setting technical problem between the pure phosphate main agent system and the highly reactive waste magnesia-carbon brick aggregate. It is necessary to introduce a retarding modifier to control the interfacial reaction rate; otherwise, industrial production cannot be implemented.

[0078] In the embodiments and comparative examples of this invention, the performance testing methods are as follows: Bulk density and apparent porosity were determined by Archimedes' water displacement method (refer to GB / T 2997-2015). The sample size was a 50mm×50mm×50mm cube, the impregnation medium was deionized water, and the weighing accuracy was 0.001g.

[0079] The room temperature flexural strength was determined by the three-point bending method (refer to GB / T 3001-2017). The sample size was a strip of 150mm×25mm×25mm with a span of 125mm. The loading rate was 0.15mm / min. The testing instrument was a CMT5105 universal testing machine.

[0080] The room temperature compressive strength was determined by the uniaxial compression method (refer to GB / T 5072-2008). The sample size was a 50mm×50mm×50mm cube, the loading rate was 1.0mm / min, and the testing instrument was a YE2000 pressure testing machine.

[0081] The flexural strength at 1400℃ was determined using a high-temperature flexural strength tester (refer to GB / T 3002-2017). The sample was heated to 1400℃ in a muffle furnace at a rate of 5℃ / min and held for 0.5h. Immediately afterward, a three-point bending test was performed with a span of 125mm.

[0082] The slag erosion resistance was determined using the static crucible method (refer to YB / T 4202-2017). A crucible hole with a diameter of 30 mm and a depth of 40 mm was pre-drilled on the sample and filled with VOD steel slag (calcium oxide content 63.34%, silicon dioxide content 2.94%, aluminum oxide content 19.82%, magnesium oxide content 6.69%, manganese oxide content 0.17%). After holding the sample at 1600℃ for 3 hours in a silicon carbide rod electric furnace, the sample was cut open and the slag line erosion depth was measured. The erosion depth of Example 1 was used as the baseline 1.00 to calculate the relative slag erosion resistance index of each sample.

[0083] Thermal shock resistance was determined by the 1100℃ water cooling cycle method (refer to GB / T 30873-2014). The sample was heated to 1100℃ in a muffle furnace at a rate of 10℃ / min and held for 20 min. Then it was immersed in 25℃ water for 5 min and the cycle was repeated until the sample cracked and failed. The number of cycles was recorded.

[0084] The residual graphite carbon content was determined by the loss on ignition method (refer to GB / T 2999-2002). The sample was held at 850℃ in a muffle furnace for 2 hours and the weight loss was measured. The residual carbon content was obtained after deducting the contribution of carbonate decomposition.

[0085] Phase composition was determined using an X-ray diffractometer (Bruker D8 Advance type, Cu-Kα radiation, scanning range 5° to 80°, scanning rate 2° / min).

[0086] The microstructure was characterized using a scanning electron microscope combined with an energy dispersive spectroscopy instrument (Zeiss Sigma 300, accelerating voltage 15kV, working distance 8.5mm).

[0087] The coefficient of variation for performance stability was obtained by calculating the ratio of the standard deviation to the mean of each performance index after 10 independent batches of repeated preparation, reflecting the batch-to-batch consistency in industrial production.

[0088] Sample preparation specifications: Three parallel samples were independently prepared for each example and comparative example. Each sample was cut from the production bricks according to the sampling specifications of GB / T7321-2017. The cut surfaces were precision ground with diamond wheels until the surface flatness was better than 0.1 mm / m. During the cutting and grinding process, the temperature rise was strictly controlled to not exceed 50℃ to avoid thermal stress damage to the bonding phase. The performance data for each batch was taken as the arithmetic mean of the three parallel samples. The standard deviation was controlled within ±5% of the mean to be considered as valid data. Otherwise, additional samples were prepared until the deviation met the requirements.

[0089] Data acquisition and statistical methods: All test data were recorded as raw waveforms and values ​​using the instrument's built-in data acquisition system. Statistical parameters such as arithmetic mean, standard deviation, and coefficient of variation were calculated using Excel software. The coefficient of variation was expressed as a percentage of the sample standard deviation to the sample mean. The relative crystallinity for XRD phase analysis was calculated using the Rietveld refinement method in BrukerDIFFRAC.SUITE software.

[0090] Error control requirements: Each test shall be performed three independent repeated measurements, and the relative range of the three results shall not exceed 8% to be considered valid. For the test of the coefficient of variation of performance stability, 10 independent batches shall be prepared for each example and comparative example, and 3 parallel samples shall be taken from each batch. The final coefficient of variation shall be obtained based on statistical calculation of 30 measurement points.

[0091] Table 1 summarizes the main performance data of Examples 1-4 and Comparative Examples 1-5, and the performance comparison bar chart is shown below. Figure 4 As shown.

[0092] Table 1. Performance Summary of Examples 1-4 and Comparative Examples 1-5

[0093] The data analysis in Table 1 is as follows: First-dimensional analysis: The bulk densities of Examples 1, 2, and 3 are 2.92, 2.88, and 2.95 g / cm³, respectively. 3 The maximum range among the three is 0.07 g / cm³. 3 (Approximately 2.4%), the range of room temperature flexural strength is 2.6 MPa (approximately 15%), and the range of slag resistance index at 1600℃ is 0.05 (approximately 5%). The three examples correspond to the median value (Example 1), the lower end (Example 2, upper limit of phosphate content 15 parts + lower limit of waste content 65 parts + lower limit of nanopowder 1 part + lower limit of residual carbon 3% + lower limit of pressure 80 MPa + lower limit of curing temperature 180℃ + upper limit of curing time 24h) of the formulation parameters, respectively. The performance of all three falls within the qualified range and the differences are smoothly transitioned.

[0094] The second dimension analysis (the impact of waste content): Under the condition that the binder, nanopowder, and mineralizer formulations and preparation processes are exactly the same, the room temperature flexural strength of Example 1 (70% waste content) increased from 12.4 MPa to 18.2 MPa (an increase of 47%) compared to Comparative Example 1 (30% waste content), the high temperature flexural strength at 1400℃ increased from 7.5 MPa to 12.5 MPa (an increase of 67%), the slag erosion resistance index increased from 0.82 to 1.00 (an increase of 22%), and the apparent porosity decreased from 14.5% to 11.5% (a decrease of 21%). This data combination proves that increasing the waste content from the existing technology limit of 30% to the range of 65% to 75% in this invention not only did not lead to a decrease in performance, but also brought about a significant improvement in performance, showing a non-linear reversal effect of high content leading to high performance.

[0095] Third-dimensional analysis (influence of binder system): Compared to Comparative Example 2 (modified asphalt binder + 250℃ baking), Example 1 (modified phosphate composite binder + 200℃ low-temperature curing), with the same waste content of 70%, showed a 69% increase in room temperature flexural strength (18.2 vs 10.8 MPa), a 102% increase in 1400℃ high-temperature flexural strength (12.5 vs 6.2 MPa), a 33% increase in slag erosion resistance index (1.00 vs 0.75), and a decrease in residual carbon oxidation weight loss rate from 2.8% in Comparative Example 2 to 0.3% in Example 1 (a reduction of 89%). This data demonstrates that the modified phosphate composite binder and low-temperature curing window used in this invention play a decisive role in the complete preservation of the residual graphite carbon layer. The complete preservation of the residual carbon layer is the physical basis for the superior performance of this invention's product in terms of slag erosion resistance and high-temperature mechanical properties compared to traditional asphalt-bonded recycled bricks.

[0096] Fourth Dimension Analysis (Necessity of Nano-Reinforced Micropowder): Compared to Comparative Example 3 (without nano-reinforced micropowder), Example 1 (3 parts of nano-reinforced micropowder) showed a decrease in apparent porosity from 19.2% to 11.5% (a 40% reduction), an increase in slag erosion resistance index from 0.68 to 1.00 (a 47% increase), and an increase in the number of water-cooled thermal shock cycles at 1100℃ from 8 to 25 (a 213% increase). This data demonstrates that the filling effect of nano-reinforced micropowder, through the formation of a phosphosilicate composite gel filling layer between the needle-like phosphate-bound phases, suppresses the apparent porosity of the matrix from over 19% in the unfilled system to below 12%, which is the core physical basis of the slag erosion resistance barrier.

[0097] The fifth dimension of analysis (necessity of residual carbon grading and screening): The performance stability variation coefficient of Example 1 (residual carbon finely graded to a specific value within the range of 3% to 12%) was 5.2%, while the performance stability variation coefficient of Comparative Example 4 (residual carbon not graded and directly mixed, with residual carbon content ranging from 3% to 15%) was as high as 26.5%. The difference in variation coefficients exceeds 5 times, proving that grading and screening of waste magnesia-carbon brick aggregate according to residual carbon content is a key process feature to ensure batch consistency in industrial production according to this invention.

[0098] Sixth dimension analysis (necessity of retarding modification): Comparative Example 5 experienced flash hardening during the wet mixing stage, resulting in process interruption and inability to form the product, thus making it impossible to obtain any performance data; while Examples 1 to 3 of this invention were able to stably produce qualified products. This result proves the essential necessity of the retarding modification component (any combination of two or more of water glass, borax, and citric acid) for the feasibility of industrial production. Without the retarding modification component, all the technical effects of this invention cannot be achieved.

[0099] The seventh dimension analysis (comprehensive performance-resource utilization benefit balance dimension): The waste content of Examples 1-3 is 70%, 65%, and 75%, respectively, corresponding to the amount of waste magnesia-carbon bricks consumed per unit product of 700 kg / t, 650 kg / t, and 750 kg / t of finished bricks. Compared with the existing technology's upper limit of 30% (corresponding to a consumption of 300 kg / t), the waste consumption is increased by 2.17 to 2.5 times. Simultaneously, the energy consumption is reduced from approximately 2.5 GJ / t of finished bricks for traditionally fired magnesia bricks to approximately 0.5 GJ / t of finished bricks for this invention (a reduction of approximately 80%), and the carbon dioxide equivalent emission per unit product is reduced by approximately 60%. Moreover, the key performance indicators of the product are comprehensively superior to or equal to those of traditional 1600℃ fired magnesia bricks. The three aspects of benefits form a comprehensive advantage of high resource utilization efficiency, high energy efficiency, and high performance efficiency, verifying the synergistic value of this invention in achieving the dual goals of industrial solid waste resource utilization and energy conservation and carbon reduction.

[0100] The core mechanism by which this invention achieves the triple goals of high dosing, low-temperature curing, and high performance lies in fully utilizing the unique microstructure of waste magnesia-carbon bricks. After long-term high-temperature service (ladle operating temperature approximately 1600℃, with single smelting cycles ranging from several hours to tens of hours), the magnesium oxide particles in the waste magnesia-carbon bricks undergo sufficient thermal activation and grain boundary opening, forming a large number of unsaturated coordinated magnesium ion surface sites. These surface sites exhibit high reactivity towards phosphate ions. Simultaneously, the residual graphitic carbon layer in the waste magnesia-carbon bricks has undergone sufficient volatilization and directional alignment during long-term service, exhibiting a porous and chemically inert structural characteristic. It does not undergo oxidative degradation in the low-temperature range of 180℃ to 220℃ (significant carbon oxidation requires a temperature not lower than 400℃ and sufficient oxygen partial pressure), thus completely retaining its non-wetting shielding function against slag.

[0101] In the modified phosphate composite binder, the phosphate main agent undergoes acid-base neutralization and coordination reactions with highly reactive magnesium oxide particles during hydration. Depending on the type of phosphate main agent, it generates strongly chemically bonded phases such as potassium magnesium phosphate hexahydrate (K-struvite, MgKPO4·6H2O), magnesium ammonium phosphate hexahydrate (struvite, MgNH4PO4·6H2O), or magnesium triphosphate pentahydrate (Mg3(PO4)2·5H2O). In the retarding modification component, water glass coats the surface of magnesium oxide particles in the form of sodium silicate gel, physically isolating the rapid diffusion of phosphate ions; borate ions in borax preferentially form a soft complex layer with magnesium ion surface sites, competitively inhibiting the instantaneous bonding of phosphate ions; the carboxylic acid groups of citric acid chelate free magnesium ions, reducing the magnesium ion concentration in the liquid phase. The synergistic effect of the three retarding modifiers extended the initial setting time from 3 minutes in the unmodified system to more than 30 minutes, but the strength development rate after final setting was not affected, and the strength continued to increase within 30 minutes to 24 hours.

[0102] Nanoparticle-reinforced powder fills the micropores in the tertiary aggregate packing system. Further silicon-phosphorus reaction occurs between nano-silica and the phosphate-bound phase, forming a dense silicon-phosphorus composite gel. Nano-alumina provides high surface energy, promoting the uniform distribution of the bound phase. The synergistic filling effect of both reduces the apparent porosity of the final product from over 19% in the unfilled system to below 12%, significantly strengthening the slag erosion resistance barrier.

[0103] The auxiliary mineralizer provides pozzolanic reactivity during the low-temperature curing stage. The active silica and alumina in metakaolin undergo a condensation reaction at the interface of the phosphate-bonded phase to form a bridging bonded phase, which further strengthens the interfacial bonding strength between the aggregate and the matrix.

[0104] The high-dosage, low-temperature curing, retarding modification, and nano-filling four-way synergistic system of the present invention is not a simple superposition of features, but an organic integration based on the unique microstructural characteristics of waste magnesia-carbon bricks.

[0105] (I) (High Dosage and Low Temperature Curing): In this invention, there is a strict causal coupling relationship between increasing the waste material dosage to the range of 65% to 75% and the low temperature curing window of 180℃ to 220℃. Only at temperatures below the residual carbon oxidation threshold can the residual porous graphite carbon layer in the waste magnesia-carbon bricks retain its non-wetting shielding function against slag. Conversely, if the baking or sintering temperature above 250℃ of the existing technology is used, the residual graphite carbon layer will undergo significant oxidation and damage, and the refractory performance inheritance function of the waste material will collapse. At this time, even a higher dosage cannot improve the product performance.

[0106] (II) (Retarding Modification and Nanofilling): In this invention, the retarding modification component extends the initial setting time of phosphate and highly reactive magnesium oxide to more than 30 minutes, while providing a sufficient time window for uniform dispersion of nano-reinforced powder, avoiding the formation of local stress concentration areas by the agglomeration of nano-reinforced powder in individual positions; the nano-reinforced powder fills the gaps in the needle-shaped phosphate-bound phase, while reducing the diffusion free space of phosphate ions in the liquid phase, which in turn promotes the orderly release of the retarding modification component. The two form a positive feedback coupling mechanism, so that the apparent porosity of the final product is reduced from more than 19% in the unfilled system to less than 12%.

[0107] (III) (Auxiliary mineralizer and gradation of tertiary aggregate): The pozzolanic activity provided by metakaolin or Class I fly ash ultrafine powder mainly acts on the interface region between fine aggregate and phosphate-bonded phase. The thickness of the bridging bonded phase is about 100nm to 300nm, which exactly matches the size difference between the fine powder particle size (≤75μm) and the phosphate needle-like crystalline phase (about 1μm to 5μm) in the tertiary aggregate, thus achieving three-level reinforcement of skeleton-interface-matrix.

[0108] (iv) (Residual carbon grading and product stability): This invention finely grades waste magnesia-carbon brick aggregates according to the residual carbon content range of 3% to 12%, so that the residual carbon content of each batch of products fluctuates within ±2%. With the precise proportion of modified phosphate composite binder, the batch performance stability variation coefficient is controlled within 7%, which meets the stability requirements of industrial mass production.

[0109] The core chemical process of the low-temperature curing reaction system involved in this invention can be described as follows.

[0110] The first stage is the phosphate dissolution and magnesium ion surface activation stage: the phosphate main agent (taking potassium dihydrogen phosphate as an example) ionizes in aqueous solution to generate potassium ions, dihydrogen phosphate ions and a small amount of hydrogen phosphate ions.

[0111] Its acid ionization reaction is as follows: potassium dihydrogen phosphate dissolves to form dihydrogen phosphate ions and releases hydrogen ions, causing the local liquid phase pH to drop to the range of 4.5 to 5.5. Simultaneously, a protonation reaction occurs on the surface of highly reactive magnesium oxide particles in the waste magnesia-carbon bricks. Magnesium oxide reacts with hydrogen ions to generate magnesium ions, which are released into the liquid phase. The reaction formula is: MgO + 2H⁺ + →Mg 2+ +H2O.

[0112] The second stage is the water glass gel shielding stage: Sodium silicate in water glass undergoes hydrolysis and condensation in an environment with decreasing pH to form silica gel, which preferentially deposits on the surface of magnesium oxide particles to form a continuous shielding layer.

[0113] The reaction can be simplified as follows: sodium silicate hydrolyzes to release hydroxide ions and form silica monomers, which then undergo condensation polymerization of silicon-oxygen-silicon bonds to form a network structure of silica gel. The thickness of this silica gel layer is approximately 50 nm to 200 nm, effectively blocking the diffusion of phosphate ions.

[0114] The third stage is the borax complexation stage: the tetraborate ions in borax hydrolyze in aqueous solution to generate boric acid and hydroxide ions. The reaction is as follows: the tetraborate ions hydrolyze with water to generate boric acid monomers. The hydroxyl groups on the boric acid monomers form soft coordination bonds with unsaturated magnesium ions on the surface of magnesium oxide. The reaction is represented as: the boric acid hydroxyl groups form magnesium-oxygen-boron coordination complexes with magnesium ions, competitively occupying potential bonding sites of phosphate ions.

[0115] The fourth stage is the citric acid chelation stage: the three carboxylic acid groups in the citric acid molecule form a stable polydentate chelate complex with magnesium ions. The reaction is as follows: the citrate ion and magnesium ions form a magnesium citrate chelate, which reduces the concentration of free magnesium ions in the liquid phase.

[0116] The fifth stage is the low-temperature curing and bonding phase formation stage: At a low-temperature curing temperature of 180℃ to 220℃, the silica gel shielding layer gradually dehydrates and densifies, the boron-oxygen bonds in the borax complex layer recombine, the carboxylic acid groups of the citric acid chelate undergo thermal decomposition, and the three types of retarding barriers are simultaneously released. Dihydrogen phosphate ions begin to react in an orderly manner with free magnesium and potassium ions, generating the main bonding phase of magnesium potassium phosphate hexahydrate. The reaction is as follows: dihydrogen phosphate ions combine with magnesium ions, potassium ions, and water molecules to form magnesium potassium phosphate hexahydrate. The generated magnesium potassium phosphate hexahydrate crystalline phase exhibits a needle-like or rod-like morphology in its microstructure, interwoven to form a continuous three-dimensional bonding network, tightly bonding the waste magnesia-carbon brick aggregate particles together.

[0117] The sixth stage is the silicon-phosphorus synergistic densification stage of nano-reinforced micropowder: nano-silica micropowder reacts with dihydrogen phosphate at a low-temperature curing temperature to generate phosphosilicate composite gel. The phosphosilicate composite gel fills the nanoscale pores between the magnesium potassium phosphate hexahydrate crystalline phase, forming a composite microstructure of needle-shaped phosphate main crystalline phase + amorphous phosphosilicate composite gel filling phase. Compared with the single phosphate bound phase, the porosity is reduced by about 30%, and the resistance to slag erosion and penetration is significantly improved.

[0118] The seventh stage is the synergistic protection stage of the residual graphite carbon layer: During the low-temperature curing reaction, the residual graphite carbon layer on the surface of the waste magnesia-carbon brick particles remains chemically inert, does not participate in the hydration reaction, and does not undergo oxidative degradation. The function of the residual graphite carbon layer in the final product is: during the service life of the product, it forms a non-wetting barrier against the slag, preventing the liquid slag from eroding and penetrating the magnesia matrix; at the same time, it provides a high thermal conductivity energy dissipation channel during rapid thermal shock, enhancing thermal shock resistance.

[0119] The eighth stage is the secondary ceramic transformation mechanism during the high-temperature service stage: When the non-fired refractory bricks of this invention are put into use in the working lining of metallurgical steel ladles, an in-situ secondary ceramic transformation process will occur when the temperature is first raised to above 1400℃. The secondary ceramic transformation can be divided into the following sub-processes: First, magnesium potassium phosphate hexahydrate undergoes staged dehydration in the range of 300℃ to 500℃, successively losing 6 water molecules in its water of crystallization and transforming into anhydrous phosphate phase; Second, the anhydrous phosphate phase undergoes structural reorganization in the range of 800℃ to 1100℃, reacting with the residual magnesium oxide particles in a solid phase to generate high-temperature stable phases such as magnesium metaphosphate and magnesium pyrophosphate; Third, at the interface between the nano-silica filling layer and the phosphate phase, magnesium silicate high-temperature stable phases such as forsterite (Mg2SiO4) and enstatite (MgSiO3) are generated in the range of 1100℃ to 1400℃. The magnesium silicate phase exhibits better chemical stability than the pure phosphate phase under the corrosive environment of molten steel slag; Fourth, the residual graphite carbon layer continuously provides a slag non-wetting shielding function under the protection of reducing slag, with only a thin layer of consumption at the micron level occurring on the working surface, and the residual carbon layer inside the brick is completely preserved.

[0120] The ninth stage is the aggregate-matrix stress release mechanism: During rapid thermal shock (e.g., a ladle being rapidly cooled from 1600°C to room temperature), the non-fired refractory bricks of this invention exhibit stress release due to the difference in thermal expansion coefficients between the waste magnesia-carbon brick aggregate and the phosphate-bonded matrix (the linear expansion coefficient of magnesia is approximately 13 × 10⁻⁶). -6 At / ℃, the phosphate-bound phase is approximately 9×10⁻⁶. -6 The presence of residual graphite carbon layers provides a stress buffer for this thermal stress. Graphite has low interlaminar shear strength (approximately 0.7 MPa), allowing interlaminar stress to be released through micro-slippage between graphite layers, thus preventing overall brittle cracking caused by stress concentration. This mechanism results in the product of this invention exhibiting significantly better thermal shock resistance (25 cycles of water cooling at 1100°C) than Comparative Example 3 (only 8 cycles) without residual carbon protection.

[0121] In this invention, the porous structure (pore size ranging from 50 nm to 500 nm) of the residual graphite carbon layer on the surface of waste magnesia-carbon brick aggregate provides a unique capillary wetting interface for the phosphate main agent solution in the modified phosphate composite binder. Driven by capillary force, the modified phosphate solution penetrates into the aggregate surface to a depth of approximately 5 μm to 20 μm along the micropores of the residual carbon layer. Within this depth range, an in-situ hydration reaction occurs to generate a phosphate-bound phase, forming a three-layer gradient bonding structure of aggregate-penetrated bonded phase-surface bonded phase. Compared to the comparative example without a residual carbon layer (i.e., the case after asphalt damage to the residual carbon in Comparative Example 2), the interfacial shear strength is increased by approximately 2.5 times. This interface wettability deepening mechanism is one of the core physical foundations for achieving high waste content + high interfacial strength in this invention.

[0122] Although embodiments of the present invention have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting the present invention. Those skilled in the art can make changes, modifications, substitutions and variations to the above embodiments within the scope of the present invention.

Claims

1. A method for preparing environmentally friendly, low-temperature curing, non-fired refractory bricks from recycled waste magnesia-carbon bricks, characterized in that, Includes the following steps: (1) The waste magnesia-carbon bricks are sorted according to the residual carbon content to obtain waste magnesia-carbon brick material batches with a residual carbon content of 3%~12%. The material batches are then crushed and graded by a vibrating screen to obtain three grades of raw materials: coarse aggregate, medium aggregate, and fine powder. The coarse aggregate, medium aggregate, and fine powder are then mixed to obtain waste magnesia-carbon brick aggregate. The waste magnesium-carbon brick aggregate is pre-coated with a composite aqueous solution of citric acid and phenolic resin for 10 to 30 minutes to resist hydration. In the composite aqueous solution of citric acid and phenolic resin, the mass concentration of citric acid is 0.5%~2%, and the mass concentration of phenolic resin is 1%~3%. (2) The waste magnesia-carbon brick aggregate, modified phosphate composite binder, nano-reinforced powder and auxiliary mineralizer are mixed to obtain a mixture; The mixture is composed of the following raw materials in parts by weight: 65-75 parts of waste magnesia-carbon brick aggregate, 8-15 parts of modified phosphate composite binder, 1-5 parts of nano-reinforced powder, and 1-3 parts of auxiliary mineralizer; The modified phosphate composite binder is composed of a phosphate-containing main agent and a retarding modifier. (3) The mixture is pressed and molded at room temperature to obtain a green body; (4) The green brick is heated and kept warm to solidify, and then naturally cooled to room temperature to obtain environmentally friendly waste magnesia-carbon bricks recycled at low temperature and non-fired refractory bricks.

2. The method for preparing environmentally friendly waste magnesia-carbon bricks through low-temperature curing and non-fired refractory bricks according to claim 1, characterized in that, When the waste magnesia-carbon bricks mentioned in step (1) are crushed, the waste magnesia-carbon bricks are first crushed by a jaw crusher to block material with a particle size of no more than 50 mm, and then crushed by an impact crusher to a particle size of no more than 10 mm. The coarse aggregate has a particle size of 1mm to 3mm, the medium aggregate has a particle size of 0.1mm to 1mm, and the fine powder has a particle size of no more than 0.075mm. The mass ratio of coarse aggregate, medium aggregate, and fine powder in the waste magnesia-carbon brick aggregate is 30~40:30~40:20~30.

3. The method for preparing environmentally friendly waste magnesia-carbon bricks through low-temperature curing and non-fired refractory bricks according to claim 1, characterized in that, The nano-reinforced powder is nano-silica and / or nano-alumina, and the specific surface area of ​​the nano-reinforced powder is not less than 50 m². 2 / g; The auxiliary mineralizer is metakaolin ultrafine powder or Class I fly ash ultrafine powder, and the specific surface area of ​​the auxiliary mineralizer is not less than 600 m². 2 / kg.

4. The preparation method of environmentally friendly waste magnesia-carbon brick recycled low-temperature curing non-fired refractory brick according to claim 1, characterized in that, The modified phosphate composite binder has a mass ratio of phosphate main agent to retarding modifier of 60~80:20~40. The phosphate main agent is any one or a mixture of potassium dihydrogen phosphate, ammonium dihydrogen phosphate, aluminum phosphate, and magnesium dihydrogen phosphate; The retarding modification component is any two or more of water glass, borax, and citric acid.

5. The preparation method of environmentally friendly waste magnesia-carbon brick recycled low-temperature curing non-fired refractory brick according to claim 1, characterized in that, The mixing in step (2) involves first dry mixing each raw material for 3 to 5 minutes, and then adding water equivalent to 3% to 8% of the total mass of the raw materials and wet mixing for 3 to 8 minutes.

6. The method for preparing environmentally friendly waste magnesia-carbon bricks through low-temperature curing and non-fired refractory bricks according to claim 1, characterized in that, The pressure applied during step (3) is 80 MPa to 120 MPa, and the density of the green body is not less than 2.80 g / cm³. 3 .

7. The preparation method of environmentally friendly waste magnesia-carbon brick recycled low-temperature curing non-fired refractory brick according to claim 1, characterized in that, The green body described in step (4) is first aged at room temperature for 24h~48h before heat preservation and curing, and then pre-dried at 50℃~80℃ for 4h~8h.

8. The method for preparing environmentally friendly waste magnesia-carbon bricks through low-temperature curing and non-fired refractory bricks according to claim 1 or 7, characterized in that, The heating temperature for heat preservation and curing in step (4) is 180℃~220℃, and the heat preservation and curing time is 8h~24h.

Citation Information

Patent Citations

  • Recycling technology for MgO-C refractory brick

    CN104529492A

  • Tundish magnesium dry material and preparation method thereof

    CN115626830A